High discount rates: - An artifact caused by poorly framed experiments or a result of people being poor and vulnerable? - Stein Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2013)
This study revisits the issue whether poverty and shocks are associated with high discount rates by using an incentive compatible Multiple Price List approach in a poor rural population in Africa where a substantial share of the population had been affected by drought in the recent rainy season. Randomized treatments included tests for present bias, magnitude effects and time horizon effects. While the study revealed significant present bias, magnitude and time horizon effects, average rates of time preference remained high after correcting for risk aversion. Exposure to drought increased the average rates of time preference by 42-47%.
Keywords: C93; D91; Q54; 330; Time preferences; poverty; climatic shocks; risk aversion; artifactual field experiment; Multiple Price List approach; Malawi